Spark ignition engine performance analysis of liquefied petroleum gas - Muhammad, Siti Sabariah; Bakar, R. A. (Institute of Physics Publishing, 2020)
Liquefied petroleum gas (LPG) consists of propane, propylene, butane and butylene. Currently propane is used as an alternative fuel to gasoline gas for internal combustion engine in vehicles. This is because the targets to achieve near zero emissions from ICE. But, there are the biggest challenges about the reduction of emissions of refining performance and fuel consumption. Thus, the analysis of engine performance of LPG in SI engine has been done. The purpose of this research paper is to analyse the engine performance of SI engine using LPG fuel instead of gasoline fuel by doing a simulation. This paper is based on the zero dimensional models with the single zone model approach. In order to develop a mathematical model, multiple heat transfer equations have been researched. In calculation performed at different engine speeds have been selected for each fuel to make comparisons from engine performance view. The simulation results will show the difference between the engine performance between gasoline and LPG such as brake power, brake torque and indicated specific fuel consumption. In conclusion, by doing a simulation analysis other parameters can be analysed and cut the costs.